Valorisation Approach for the Soybean By-Product Okara Using High Hydrostatic Pressure - Mateos-Aparicio, Inmaculada; Pérez-López, Elena; Rupérez, Pilar (Current Nutrition & Food Science, 2019)
Okara is a perishable, cheap and abundant by-product derived from soybean after extracting the soluble fraction for tofu or soybean drink, mainly known as soymilk, production. Nowadays, Okara is mostly discarded: landfill and incineration, but a useful alternative for valorisation would be to use it as a valuable source of dietary fibre. However, it presents low soluble dietary fibre (SDF) content responsible for prebiotic and anti-carcinogenic effects, so an easy industrial transformation to maximize its SDF content would be most interesting for this purpose. Different approaches can be used to increase SDF content, such as chemical or enzymatic treatments with food-grade enzymes at atmospheric pressure, but these conventional methods present some disadvantages as that the chemical procedures are pollutant and the extractions normally are incomplete, and the enzymatic methods could be expensive to scale-up. On the other hand, currently, consumers are demanding for safer, more natural and minimally-processed foods. This request has led researchers and manufacturers to develop new technologies, and within these, high hydrostatic pressure (HHP) is one of the top-10 most popular emerging technologies applied in the field of food science. The effect of HHP, and more recently, the combined effect of HHP and enzymatic treatment on okara by-product have been studied, showing that this novel approach, should also be considered in order to stabilise other agro-food byproducts -due to their perishable character- as well as to improve the functionality of the rich-ininsoluble dietary fibre from vegetable residues.
Keywords: prebiotic